Effectiveness Of Community Program Implementation For Food Business Development Among Rice Producer (Case Study In Gapoktan Mutual Cooperationvillage, Pertapan Maduretno Sidoarjo District Park) - Nur Farida Kusumawati Farida; Budi Utomo; Nanik Indah Wulandari (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2023)
The People's Food Business Development Activity (CFBD) is one of the government's efforts to maintain price stability at the level of farmers, producers and consumers. This study aims to describe the implementation of the Gapoktan Mutual cooperationCommunity Food Business Development (CFBD) program in Pertapan Maduretno Village, Taman District, Sidoarjo Regency. The Association of Farmers Groups (GAPOKTAN) is a collection of various groups of farmers who come together and work together to increase economies of scale and business efficiency. This research is descriptive in nature with two quantitative and qualitative approaches (mixed method) wherein this research is shown quantitatively and qualitatively (sequentially/sequentially) the most important quantitative with a deductive direction, after completion is pursued with qualitative. Based on the results of calculating the efficiency of managing CFBD funds which have been carried out for 3 years, from 2018 to the present, the CFBD program in Mutual cooperationGapoktan, Maduretno Pertapan village has an average efficiency level of 73%.